Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1097/inf.0000000000002733
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Decline of the Glomerular Filtration Rate in HIV-infected Children Treated With Tenofovir Disoproxil Fumarate-based Regimens in West and Central Africa

Abstract: A cross-sectional study of 358 HIV-1-infected children and adolescents living in Sub-Saharan Africa treated with tenofovir disoproxil fumarate-based regimens for a median of 1.5 interquartile range [0.6–3.1 years] showed a loss of glomerular filtration rate estimated to be 0.41 mL/min/1.73 m2 per month of treatment. In contrast, there was no decrease depending on the duration of the previous antiretroviral treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Estimated GFR (eGFR) was used in 13 studies alone and in combination with markers of kidney damage (6, 33, 4447, 5153, 5558). Five studies used an eGFR cut-off of <60ml/min/1.73m 2 (4446, 55, 57), two used this cutoff alone without any marker of kidney damage (45, 57) and six used a cut-off of <90ml/min/1.73m 2 (6, 33, 47, 51, 53, 58). These studies showed a CKD prevalence between 0.8% and 35.9%.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Estimated GFR (eGFR) was used in 13 studies alone and in combination with markers of kidney damage (6, 33, 4447, 5153, 5558). Five studies used an eGFR cut-off of <60ml/min/1.73m 2 (4446, 55, 57), two used this cutoff alone without any marker of kidney damage (45, 57) and six used a cut-off of <90ml/min/1.73m 2 (6, 33, 47, 51, 53, 58). These studies showed a CKD prevalence between 0.8% and 35.9%.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies recruited only YPLHIV who were perinatally infected (6, 33, 51). Among the studies that recruited ART-experienced participants, two included only those on TDF-containing regimens (45, 53). Four studies enrolled HIV-negative control groups from the general population (6, 33, 56, 57).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations